PENGARUH INVESTASI SUMBER DAYA MANUSIA TERHADAP PERTUMBUHAN EKONOMI - Teguh Dwiarsyah; Alfansi Lizar; Yefriza Yefriza (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2021)
The objectives of this study include the analysis of how the effect of Human Capital and other determinants on Economic Growth in Bengkulu Province. The analytical method . using panel data regression statistical analysis tools for analyze how the influence of Human Capital (Human Capital) and other determinants of economic growth in Bengkulu Province. The results showed that the average length of schooling (X1), the workforce had the skills (X2) and investment (X9 had a significant positive effect on economic growth. While the Life Expectancy Rate (X5), Government Expenditure in the Health (X7) significant negative impact on economic growth. (X2), the Workforce has no skills (X3) Government Expenditures in the Education (X4),) Maternal Mortality Rate (X6) and Unemployment (X8) have no significant effect on economic growth in Bengkulu . Implication: development that prioritizes improving the quality of human resources can be used as one of the regional development strategies in Indonesia, because the impact can not only create economic growth but also increase income distribution, so that the development objectives of growth and equity can be achieved simultaneously. There are still districts that have an education budget of less than 20% and health less than 10% need to be noted and improved so that later it is hoped that it can produce quality human resources so that districts / cities and Bengkulu Province can become more advanced and catch up with the Province.